Design variables for optimizing adaptive metacomposite made of shunted piezoelectric patches distribution. (April 2016) - Tateo, F; Collet, M; Ouisse, M; Cunefare, KA
A two-dimensional array of a piezoelectric transducer shunted on a negative capacitance circuit is designed and applied to achieve broadband vibration reduction of a flexible plate over tunable frequency bands. Each surface-bonded patch is connected to a single independent negative capacitance synthetic circuit. A finite-element-based design methodology is used to predict and optimize the attenuation properties of the smart structure. The predictions are then experimentally validated by measuring the harmonic response of the plate and evaluating some derived quantity such as the loss factor and the kinetic energy ratio. The validated model is finally used to explore different configurations with the aim of defining some useful design criteria. The results obtained clearly show how the proposed strategy represents a robust and effective solution for the control of vibrations in complex structures.